"It gets better. It can´t be worse than what we have been through." Family accounts of the minimally conscious state. (6th December 2018) - Løvstad, Marianne; Solbrække, Kari Nyheim; Kirkevold, Marit; Geard, Anne; Hauger, Solveig Lægreid; Schanke, Anne-Kristine
ABSTRACT: Objectives : The aim of this qualitative study was to explore family life when a family member is in a chronic minimally conscious state (MCS). Experiences with the health care system were also explored. Methods : As part of a larger qualitative study of family life after a family member suffers severe physical injury, we conducted a focus group interview with five family members of three patients in a chronic MCS. The participants included three mothers, one father, and one sibling. The length of time since the brain injuries was four, four, and ten years. A thematic analysis was conducted. Results : Three main themes emerged. Each family reflected on the challenges of maintaining family unity. They also revealed how they had dealt with the ambiguity and severity of the situation, including the communication with the health care system. Finally, they described their journeys back toward a normal, everyday family life. Conclusions : The findings demonstrate challenges faced by family members but also their capacity to withstand and overcome adversity. Clinicians are reminded to maintain a long-term perspective and understand the importance of helping families adjust, maintain hope for a better future, and mitigate their psychological pain.